2007
DOI: 10.1080/01612840701354596
|View full text |Cite
|
Sign up to set email alerts
|

Consumer and Carer Participation in Mental Health Care: The Carer's Perspective: Part 1—the Importance of Respect and Collaboration

Abstract: The role of family carers in the delivery of mental health services in Australia has become more than an advantage over not having this sort of participation. Increasingly the involvement of non-paid carers (family members and significant others) has been recognised as central to the smooth delivery of care and treatment. Notwithstanding this acknowledgment, there is very little discussion of carer participation in mental health care delivery within the literature. The limited research in this area suggests th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 18 publications
3
61
2
Order By: Relevance
“…The value of knowledge is in line with the findings of Andershed and Ternestedt (1999), who stressed that "to know" could be seen not only as a part of caring but also as a prerequisite for meaningful involvement in the care. Collaboration between natural and psychiatric professional health care has been emphasized as important (Ewertzon et al, 2010;Goodwin & Happell, 2007) yet generally, in our study, the fathers did not find mental health professionals helpful or supportive. Similar findings were reported in studies by Clarke and Winsor (2010) and Reid, Lloyd, and de Groot (2005).…”
Section: Discussioncontrasting
confidence: 66%
“…The value of knowledge is in line with the findings of Andershed and Ternestedt (1999), who stressed that "to know" could be seen not only as a part of caring but also as a prerequisite for meaningful involvement in the care. Collaboration between natural and psychiatric professional health care has been emphasized as important (Ewertzon et al, 2010;Goodwin & Happell, 2007) yet generally, in our study, the fathers did not find mental health professionals helpful or supportive. Similar findings were reported in studies by Clarke and Winsor (2010) and Reid, Lloyd, and de Groot (2005).…”
Section: Discussioncontrasting
confidence: 66%
“…Similar studies outside Norway confirm that NOK to adults as well as adolescents/children also experience lack of, or inconsistent, support and involvement [1, 6, 7, 14], and experience feelings of powerlessness and alienation by the way they are met [22]. …”
Section: Discussionmentioning
confidence: 72%
“…They often play an important role as informal caregivers contributing to improvement of the patient’s health [15]. Furthermore, they are co-sufferers having been deeply involved in their family member’s suffering for years, and may themselves carry symptoms and ailments as a result of what they have been going through [68].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings also suggest that psychoeducational interventions should consider gender differences and family roles. In Australia, Goodwin and Happel 142,143 found that family members and significant others contribute to the smooth delivery of care and treatment, particularly when they feel respected and are included in communications, but the researchers also observed a lack of discussion regarding carer participation in health care delivery.…”
Section: Family and Carers: Needs And Preferencesmentioning
confidence: 99%